DIAGNOSTIC ACCURACY AND REFERRAL PERFORMANCE OF TELEMEDICINE FOR DIABETIC RETINOPATHY SCREENING AT PRIMARY HEALTH CARE FACILITIES IN NGHE AN (Vietnam Journal of Community Medicine, 2026)
Background: Diabetic retinopathy (DR) screening at the primary health care level remains challenging because of limited access to ophthalmic specialists. Although telemedicine has demonstrated high diagnostic accuracy, evidence regarding its role in supporting referral decisions within community-based screening programmes is still limited.Objective: To evaluate the diagnostic accuracy and referral-support performance of a telemedicine-based diabetic retinopathy screening programme at primary health care facilities in Nghe An Province, Vietnam.Methods: A community-based cross-sectional diagnostic accuracy study was conducted among 360 adults with type 2 diabetes. Digital fundus photographs were obtained at primary health care facilities and graded remotely using a telemedicine platform. Dilated fundus examination by retinal specialists using slit-lamp biomicroscopy with a Volk 90D lens served as the reference standard. Image gradability, sensitivity, specificity, predictive values, Cohen's kappa, and agreement in referral decisions were assessed.Results: Of 360 participants, 330 image sets (91.7%) were gradable. For diabetic retinopathy detection, telemedicine achieved a sensitivity of 93.9%, specificity of 90.0%, positive predictive value of 80.2%, negative predictive value of 97.2%, and a Cohen's kappa of 0.78. High agreement was observed between telemedicine and direct examination regarding referral decisions. Disagreements were mainly related to ungradable images and early-stage retinal lesions.Conclusions: Telemedicine demonstrated high diagnostic accuracy and substantial agreement in referral decision-making. These findings support the integration of telemedicine as a referral-support system, rather than merely an image-reading tool, within diabetic retinopathy screening programmes at primary health care facilities.
Keywords: diabetic retinopathy; telemedicine; referral; screening; diagnostic accuracy; primary health care.